ANTIBIOTIC RESISTANCE IN PEDIATRIC POPULATIONS IN PAKISTAN - Dr Bilal Sher Khan; Dr Atiq Ur Rahman; Dr Sher Alam Khan; Khalida Shaheen; Dr Muhammad Fayaz; Farkhanda Jabeen (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Introduction: Antibiotic resistance in pediatric populations is an emerging global health threat, particularly in low- and middle-income countries like Pakistan. Increasing resistance complicates treatment and leads to higher morbidity and mortality in children. Objective: To investigate the prevalence and patterns of antibiotic resistance among bacterial pathogens isolated from pediatric patients in a tertiary hospital in Pakistan. Materials and Method: This cross-sectional study was conducted at Combined Military Hospital Abbottabad, Pakistan, from July 2022 to December 2022. Pediatric patients aged 0–18 years with confirmed bacterial infections were included. Samples were cultured, and antibiotic susceptibility testing was performed using standardized methods. Results: The study showed that many strains of Escherichia coli, Staphylococcus aureus (including MRSA), and Klebsiella pneumoniae had a high resistance rate. Multidrug resistance was common, particularly against commonly used antibiotics such as ampicillin, ciprofloxacin, and cephalosporins. MRSA isolates showed significant resistance to clindamycin and trimethoprim-sulfamethoxazole. Conclusion: Antibiotic resistance is alarmingly high in pediatric infections in Pakistan. Enhanced antimicrobial stewardship, improved diagnostics, vaccination, and national surveillance are essential to curb this threat and ensure effective treatment.